حكم وآثار اقتران اسم الله (العليم) باسم الله (القدير) في القرآن الكريم:دراسة تحليلية: Wisdom and effects of the association of Allah’s names, Al’Alim with Al-Qadeer in the Holy Qur’an - Mouhran, Nasser Abdelfadeil Abdelhafez; Bey , Abdelali Zekkoub (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث تناولت الدراسة حكم وآثار اقتران اسم الله (العليم) باسم الله (القدير) في القرآن الكريم، وتكمن إشكالية الدراسة في الضرورة الملحة لدراسة اقتران الأسماء الحسنى لمعرفة أوجه الحكمة اللغوية والمعنوية، والوقوف على أثرها الشرعي والتربوي، وهدفت الدراسة إلى بيان مفهوم اقتران الأسماء الحسنى في القرآن الكريم أهميته، ومعرفة معنى اسمي العليم والقدير، وبيان مواضع اقتران اسم الله العليم باسم الله القدير في القرآن الكريم، والكشف عن حكمة اقترانهما، واستنباط آثار اقتران هذين الاسمين الجليلين في القرآن الكريم. واعتمدت الدراسة المنهج الاستقرائي والاستنباطي لتحقيق أهدافها، وأسفرت الدراسة عن نتائج أهمها: اقتران اسم الله العليم باسم الله القدير في أربعة مواضع من القرآن الكريم في سور مكية، ولم يقترن اسم الله العليم في هذه السور باسم آخر، وكان متقدما في كل المواضع، ولهذا الاقتران حكم عديدة أن تسيير الله تعالى لأمر الخلائق جميعها ناشئ عن علم الله وقدرته، ومتوقف عليهما، وأن الإنسان في مراحله يتنقل بين قوة وضعف، وبين علم وجهل، أما الله جل جلاله فالعلم والقدرة ثابتة لا تتغير أبدا، كما أن الجمع بين العلم والقدرة يدل على الحكمة والإرادة، وإثبات البعث واليوم الآخر، كما يترتب على اقتران اسمي العليم والقدير آثار كثيرة، ومنها: معرفة الله تعالى ومحبته، وتحقيق المراتب العالية من العبودية، وتزكية النفس، وحسن الخلق والبعد عن الظلم، والرضا بالقضاء والقدر، والإيمان باليوم الآخر. وأوصى الباحث الهيئات الأكاديمية الشرعية واللغوية بعمل موسوعات علمية تتناول اقتران جميع الأسماء الحسنى في القرآن واستنباط الحكم والآثار منها. ABSTRACT This research studied the wisdom and effects of the association of Allah’s names, Al’Alim with Al-Qadeer in the Holy Qur’an. The study problem lies in the urgent necessity to discuss the association of the Beautiful Names to know the aspects of moral and linguistic wisdom and consider the educational and legal effects. The study aims at clarifying the concept of the association of the Beautiful Names in the Holy Qur’an, knowing the meaning of the two names: Al’Alim and Al-Qadeer, stating the positions of the association of Allah’s names, Al’Alim with Al-Qadeer in the Holy Qur’an, disclosing the wisdom beyond their association and deducing the effects of the association of these two sublime names in the Holy Qur’an. The study adopted the inductive and deductive methodologies to achieve its objectives. The study found the following results. The association of Allah’s names, Al’Alim and Al-Qadeer, occurred in four places of the Holy Qur’an in Makkan chapters. Allah’s name, Al’Alim, in these Suras was not associated with another name. and it was mentioned first in all positions. This association has many principles: Allah Almighty’s management of the affairs of all creatures arises from Allah’s I’lm (knowledge) and Qudrah (Powerul Capability), and depends on them. In addition, man in his stages moves between strength and weakness, and between knowledge and ignorance, but Allah the Most High has constant I’lm and Qudrah and they never change. association of I’lm and Qudrah denotes wisdom and will, and proves the resurrection and the Last Day. The association of the two names of Al’Alim and Al-Qadeer results in many effects, including: knowledge of Allah Almighty and His love, achievement of high levels of servitude, self-purification, good manners and avoiding injustice, contentment with fate and destiny, and belief in the Last Day. The researcher urges the legal and linguistic academic bodies to make academic encyclopedias dealing with the associations of all the Beautiful Names in the Qur’an and deducing the wisdom and effects from them.